PENERAPAN METODE LOGIKA FUZZY DALAM ANALISIS KEPUASAN MAHASISWA TERHADAP SISTEM PERKULIAHAN ONLINE - Agung Aprianto; Indra Kanedi; Prahasti Prahasti (Jurnal Media Infotama, 2023)
Abstract-In an effort to improve service quality, facilities and infrastructure are needed to support the service process provided. Where there needs to be proper treatment starting from the input, process, to the output of the services provided. Good relations and communication with the community are needed in an effort to maintain the continuity of a continuous service process. In assisting the analysis of student satisfaction, a fuzzy logic method is applied, namely Fuzzy Tsukamoto. The Tsukamoto method is an extension of monotone reasoning. In the Tsukamoto method, every consequence of a rule in the form of an If-Then must be represented by a fuzzy set with a monotonous membership function. The results of this study are that the application of Student Online Learning Satisfaction Analysis using the Tsukamoto algorithm has been successfully implemented and produces rules that are in accordance with what is desired. Primari Key : Application, Fuzzy Logic, Student Satisfaction.